2007
DOI: 10.1093/ndt/gfm390
|View full text |Cite
|
Sign up to set email alerts
|

Ciclosporin-induced hypertension is associated with increased sodium transporter of the loop of Henle (NKCC2)

Abstract: Our results pointed to the thick ascending limb of the loop of Henle as an important site of sodium retention in cyclosporine-induced hypertension. This data may have potential clinical implications for the treatment of hypertension induced by cyclosporine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 20 publications
3
23
1
1
Order By: Relevance
“…The abundance of Na-K-ATPase α 1 -subunit protein was not significantly changed, and NKCC2 was unchanged in cortex but remarkably increased in medulla (data not shown). The latter finding is consistent with the recent report by Esteva-Font et al [23]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The abundance of Na-K-ATPase α 1 -subunit protein was not significantly changed, and NKCC2 was unchanged in cortex but remarkably increased in medulla (data not shown). The latter finding is consistent with the recent report by Esteva-Font et al [23]. …”
Section: Discussionsupporting
confidence: 94%
“…Alteration of renal sodium transporters was previously reported in cyclosporine-treated rats [22,23]. Lim et al [22] used cyclosporine (15 mg/kg BW) subcutaneously for 28 days in rats fed low-salt diet, and found nonselective downregulation of NKCC2, NCC and Na-K-ATPase.…”
Section: Discussionmentioning
confidence: 89%
“…An experimental model of hypertension induced by CsA showed an increase in NKCC2 in rat kidneys [10]. Tacrolimus is involved in renal NCC activation associated with hypertension [11].…”
Section: Discussionmentioning
confidence: 99%
“…In cultured cells, CsA induced an increase in bumetanide-sensitive sodium potassium-2 chloride cotransporter (NKCC2) activity [9]. On the other hand, a previous study from our laboratory showed that in rats with CsA-induced hypertension, NKCC2 protein and mRNA expression levels were markedly increased in the kidneys [10]. Hoorn et al [11] reported that tacrolimus-induced hypertension was mediated by sodium chloride cotransporter (NCC) activation in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Esteva-Font et al [33] demonstrated an increase in the Na-K-2Cl (NKCC2) cotransporter in the loop of Henle in rats treated with CsA (25 mg/kg/day IP for 7 days). Lee et al [34] demonstrated a decrease in Na-Cl cotransporter in renal cortex of rats treated with CsA and also demonstrated that occludin was also increased in rat kidneys exposed to CsA.…”
Section: Csa and Srl: In Vivo Experimental Studiesmentioning
confidence: 99%